Comparative evaluation of dental and skeletal fluorosis in an endemic fluorosed district, Salem, Tamil Nadu - Maya Ramesh; N Malathi; K Ramesh; Rita Mary Aruna; Sarah Kuruvilla (Wolters Kluwer Medknow Publications, 2017)
Background: High levels of fluoride in the drinking water, especially ground water, results in skeletal fluorosis which involves the bone and major joints. This study was conducted to assess the prevalence of skeletal fluorosis to compare with dental fluorosis in an endemically fluorosed population in the District of Salem, Tamil Nadu. Materials and Methods: Institutional ethical clearance was obtained. A total of 206 patients who reported to the Department of Hematology for blood investigations were the participants in this study. Age, sex, place, weight, height, dental fluorosis, and skeletal complaints were noted down. Body mass index was calculated, and statistical analysis was performed. Results: Dental fluorosis was present in 63.1% and absent in 36.9% of the samples reported. Skeletal fluorosis was present in 24.8% and was absent in 75.2%. A large number of the patients had knee pain and difficulty in bending. Chi-square test was used for statistical analysis. Skeletal fluorosis and age were compared and P value was 0.00 and was significant. Dental fluorosis and skeletal fluorosis were compared and P value was found to be 0.000 and significant. Discussion and Conclusion: There is a need to take measures to prevent dental and skeletal fluorosis among the residents of Salem district. Calcium balance should be maintained, and fluoride intake should be minimized to reduce the symptoms. The government should provide water with low fluoride level for drinking and cooking. Once the symptoms develop, treatment largely remains symptomatic, using analgesics and physiotherapy.